Research on optimal scheduling of photovoltaic cluster based on game pricing. (July 2022) - Li, Runkang; Pan, Weiguo; Yan, Ting; Wang, Kai; Tang, Xin
Abstract: With the promotion of China's "peak carbon and carbon neutrality" target, PV power generation is gradually entering the era of price parity, and cost will no longer be the main obstacle to its scale development, but grid consumption will become the main factor to restrict its further development. In order to further promote the consumption of PV and realize the low-carbon transformation of microgrid, this paper establishes a game pricing model led by Photovoltaic Cluster (PVC) based on the response of power demand, carries out the research on the optimal scheduling of PV in microgrid by establishing the game relationship among grid, PVC and users. Firstly, a new IEEE 33-node arithmetic simulation model is built, and secondly, three PVCs are divided among the nodes, and the feasibility of the model is verified by solving the optimal tariff strategy through genetic algorithm. The final results show that the optimal scheduling method is effective in meeting the demand response of users in PVCs while reducing the cost of electricity consumption and promoting the local consumption of PV; in addition, after increasing the proportion of PV access, PV will become the main supplier of electricity and the operation mode of PVCs will be free from dependence on the grid.